Asymmetric Macroeconomic Shocks and Asset Price Behaviors in Selected African Countries - Olanrewaju, Saliu Mojeed; Oladipo, Ogunleye Edward (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study examines the relationship between Asset prices (Stock and Real estate prices) and Macroeconomic variables in four selected African countries. The study employs the Westerlund Error Correction Based Panel Cointegration test and Eight-variable Structural Vector Autoregressive model to examine the relationship between asset prices and macroeconomic variables. Findings from the study confirm that no long-run relationship exists between both Asset prices and macroeconomic variables. The study equally reveals that portfolio diversification benefits of both stock and real estate markets are more pronounced in the period of a boom than the recession period in Africa. The results also show that GDP growth rate shock exerts a significant impact on both asset prices during expansion and recession periods. The study reveals that foreign interest rates and World oil price shocks are better predictors of both stock and real estate prices during the crisis period than in the expansion period.